Rola sektora usług w procesie produkcji i reprodukcji społecznej - Majchrzak, Magdalena (Space – Society – Economy, 2008)
The role of the service sector in the national economy can be defined only after analyzing its influence on the process of social and economic development. Service in remarkably extent conditioning economic, social and cultural process stay in close connection with the social and economic changes. The rank of service development is one of criterion grading the level of social and economic development of the state. That is why economic function of service must be regarded as a necessary factor in the process of production and social reproduction. It can be seen in all phases social and economic: production, division, exchange and consumption. The service sector development needs to be recognized as a everlasting process. However one needs to underline that the base of existence and what relates to it, also the growth of GNP must be the product which may be improved or enabled by services. The development of service sector is one of the tendencies occurring in contemporary economies. The service sector is a huge area of human activity what is testified by its fulfilled different functions.